Pendidikan Islam pada Zaman Klasik: Masa Rasulullah Saw dan Khulafaur Rasyidin - Siti Hadiyanti Dini Islamiati; Andriyani; Dede Rosyada; Nurmalia Lusida (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Islamic education was crucial in fostering a robust Islamic culture during the Khulafaur Rashidin era (11-40 AH/632-661 AD). The caliphs, including Abu Bakr Ash-Shiddiq, Umar bin Khattab, Uthman bin Affan, and Ali bin Abi Talib, continued the Prophet's purpose of spreading Islam, strengthening faith, and building a just and civilised society. The Hadith and the Quran are the main sources of knowledge, covering topics like as religion, ethics, legal concepts, and the Arabic language. Mosques often incorporate teaching methods like as examples, discussions, lectures, and question and answer sessions. This study employs a qualitative methodology that focuses on historical and descriptive analysis. The data were gathered by conducting a comprehensive review of primary and secondary sources pertaining to the Khulafaur Rashidin era. The historical documents underwent interpretation and critical evaluation, while the perspectives of historians were compared. The caliphs systematised the Quran, implemented a structured administrative framework, and facilitated the spread of education to additional regions such as Persia, Egypt, and Sham. The institutionalisation of education commenced with the advent of madrasas and kuttabs. Education not only emphasised religion but also incorporated diverse fields to cultivate an enlightened and virtuous society. The education system established during the period of the Khulafaur Rashidin played a crucial role in the future advancement of Islamic education. It produced a generation of Muslims who were well-equipped to confront the problems of their era and make valuable contributions to human civilization. The current state of Islamic education demonstrates that the integration of religious principles and scientific knowledge may cultivate persons with robust moral character and exceptional abilities.